Особливості спадкування за законом в Україні - Піцик, X.3. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Данная статья посвящена вопросу о наследовании по закону. Автор высказывает собственную точку зрения на особенности наследования по закону в Украине. A given article was devoted to the question about the inheritance according to the law. The author offers his own vision of the peculiarities of the inheritance according to the law in Ukraine.